Evidence of microbial translocation associated with perturbations in T cell and antigen-presenting cell homeostasis in hookworm infections. - Palakkal Jovvian George; Rajamanickam Anuradha; Nathella Pavan Kumar; Vasanthapuram Kumaraswami; Thomas B Nutman; Subash Babu (Public Library of Science (PLoS), 2012)
Microbial translocation (MT) is the process by which microbes or microbial products translocate from the intestine to the systemic circulation. MT is a common cause of systemic immune activation in HIV infection and is associated with reduced frequencies of CD4(+) T cells; no data exist, however, on the role of MT in intestinal helminth infections.We measured the plasma levels of MT markers, acute-phase proteins, and pro- and anti-inflammatory cytokines in individuals with or without hookworm infections. We also estimated the absolute counts of CD4(+) and CD8(+) T cells as well as the frequencies of memory T cell and dendritic cell subsets. Finally, we also measured the levels of all of these parameters in a subset of individuals following treatment of hookworm infection.Our data suggest that hookworm infection is characterized by increased levels of markers associated with MT but not acute-phase proteins nor pro-inflammatory cytokines. Hookworm infections were also associated with increased levels of the anti-inflammatory cytokine--IL-10, which was positively correlated with levels of lipopolysaccharide (LPS). In addition, MT was associated with decreased numbers of CD8(+) T cells and diminished frequencies of particular dendritic cell subsets. Antihelmintic treatment of hookworm infection resulted in reversal of some of the hematologic and microbiologic alterations.Our data provide compelling evidence for MT in a human intestinal helminth infection and its association with perturbations in the T cell and antigen-presenting cell compartments of the immune system. Our data also reveal that at least one dominant counter-regulatory mechanism i.e. increased IL-10 production might potentially protect against systemic immune activation in hookworm infections.